Melatonin synthesis in and uptake by mitochondria: implications for diseased cells with dysfunctional mitochondria - Reiter, Russel (2021)
Although there is one exception (red blood cells), the lack of energy (ATP) provided by mitochondrial oxidative phosphorylation (OXPHOS) would not be compatible with the long-term survival of normal cells. During conventional metabolism, pyruvate, the cytosolic glycolysis product, enters mitochondria where it is metabolized to acetyl-coenzyme A (acetyl-CoA) under the influence of the enzyme pyruvate dehydrogenase complex (PDC). Acetyl-CoA makes an important contribution to the tricarboxylic acid (TCA) cycle which feeds NADH and FADH2 to the respiratory chain which benefits ATP´s generation by OXPHOS. In some diseased cells, however, pyruvate metabolism becomes aberrant since its transport into the mitochondria is blunted due to the downregulation of PDC due to its inhibition by pyruvate dehydrogenase kinase (PDK), which is upregulated by hypoxia-inducible factor 1 (HIF-1). Therefore, pyruvate undergoes fermentation to lactate in the cytosol. This alternate pathway of pyruvate metabolism is known as the Warburg effect, named after the individual who discovered it, Otto Warburg [1]. Since pyruvate does not enter the mitochondria, mitochondrial ATP synthesis is depressed. Warburg-type metabolism, however, compensates for this by rapidly, albeit inefficiently, synthesizing ATP in the cytosol. Warburg metabolism (also known as aerobic glycolysis) is almost always associated with pathological cells.